"Every" Student Succeeds? Academic Trends at the Intersection of (Long-Term) English Learner and IEP Status. Issue 1 (2nd January 2023) - Sahakyan, Narek; Poole, Glenn
Abstract: In this study, we describe long-term trends in students' academic performance, documenting persistent and systematic disparities in academic outcomes across several student subgroups. We leverage administrative data from longitudinal student records to examine academic outcomes for English learners (ELs), students with Individualized Education Plans (IEPs), and dual-identified students (ELs with IEPs) enrolled in one U.S. state within the last decade, spanning the years 2009 to 2019. Adopting a lens of intersectionality and using descriptive statistics in a cohort-sequential design, we examine reclassification rates that shape the long-term EL (LTEL) subgroup. Grouping students based on whether they were (ever) identified as an EL or as having a disability, we also report on academic content (Reading/ELA and Mathematics) proficiency rates across time for these subgroups. Summarizing the records of over half a million students starting school across six years (2009–2014) and four elementary grades (K-3) nested in 24 independent cohorts, our findings show that, on average, dual-identified students' rates of LTEL identification are almost twice that of ELs without disabilities, and that only a very small proportion of dual-identified students achieve proficiency in academic content. Our results raise questions and concerns regarding the adequacy and alignment of federal, state, district, and school-level policies and resources that govern the education of English learners, students with disabilities, and especially dual-identified students.